2016
DOI: 10.1158/0008-5472.can-15-3278
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Cancer and Aging

Abstract: DNA methylation is known to be abnormal in all forms of cancer, but it is not really understood how this occurs and what is its role in tumorigenesis. In this review, we take a wide view of this problem by analyzing the strategies involved in setting up normal DNA methylation patterns and understanding how this stable epigenetic mark works to prevent gene activation during development. Aberrant DNA methylation in cancer can be generated either prior to or following cell transformation through mutations. Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
498
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 700 publications
(521 citation statements)
references
References 33 publications
18
498
0
5
Order By: Relevance
“…Intriguingly, the chromatin signature of DNA hypomethylation in cancer was substantially different, being primarily enriched in the posttranslational repressive histone modification H3K9me3, a relationship that has been investigated in colon and breast cancer (Berman et al., 2011; Hon et al., 2012). This observation might be conceptually relevant because DNA methylation has been proposed to be a molecular link between aging and cancer (Fraga, Agrelo & Esteller, 2007; Klutstein, Nejman, Greenfield & Cedar, 2016). However, our results suggest that the role of DNA methylation as a possible link between aging and cancer is more complex than previously proposed.…”
Section: Discussionmentioning
confidence: 98%
“…Intriguingly, the chromatin signature of DNA hypomethylation in cancer was substantially different, being primarily enriched in the posttranslational repressive histone modification H3K9me3, a relationship that has been investigated in colon and breast cancer (Berman et al., 2011; Hon et al., 2012). This observation might be conceptually relevant because DNA methylation has been proposed to be a molecular link between aging and cancer (Fraga, Agrelo & Esteller, 2007; Klutstein, Nejman, Greenfield & Cedar, 2016). However, our results suggest that the role of DNA methylation as a possible link between aging and cancer is more complex than previously proposed.…”
Section: Discussionmentioning
confidence: 98%
“…It has been over 40 years since abnormal DNA methylation was first identified in tumor cells (31). Hypomethylation and gene-specific hypermethylation have since been observed in all detected tumor types (32). Currently, DNA demethylation drugs including decitabine and azacytidine are clinically used to treat myelodysplastic syndrome (33).…”
Section: Discussionmentioning
confidence: 99%
“…There is now considerable evidence demonstrating that abnormal methylation in normal tissues actually precedes the onset of tumors (11), and this early marker can be observed in individual crypts of the colon (28), in aging stem cells from the hematopoietic system (13) and in skin (29), raising the possibility that tumors themselves may evolve from normal cells that have already undergone excess de novo modification (30). In keeping with this idea, we have shown that tissue methylation is concentrated in a small number of individual CpG-island molecules, perhaps indicative of a fraction of cells that have undergone abnormal methylation (Table 1 and Fig.…”
Section: Significancementioning
confidence: 99%